Previsibilidade decisória - A busca de sentença que satisfaça os atores do direito - Rocha Filho, Sylvio do Amaral (2005)
ABSTRACT We will try to demonstrate, and that is the most difficult part, that it is the Human Feeling which decides, hefts, appreciates, esteems, attributes value, concludes, sentences; that Reason says how much something measures and the Feeling says how much it is worth; that Reality and the things are constructed by us in our mind; that they are worth and specified by the Feeling. And this is why there are no law operator but law actors. We will affirm that when the cult of the reason was established, we were taught that the Feeling, activity considered till now like minor, should be censured, omitted, despised, plastered, manacled: but it is worthless, it is always there to accomplish its role and there is no way to ignore it; that because its role was never understood, the Feeling (on the contrary of the Reason) did not grow nor become refined, and that it causes problems to human being. We will try to show that in a conflict there are failures in the communication between the parts; that the feeling is a mean of communication; that in the analysis of the conflict the Feelings that caused rupture, appear; that this communication needs to be re-established; that the Law Actors (the parts, the lawyers, the judges ) show themselves in the Judicial Proceedings supported by their Feelings and that, after all, in the actual judiciary system will prevail as definitive solution the one determined by the feeling of the Judge, and that may, or not , provoke more problems. We will try to defend the position that sentence should not only finish the proceedings, but finish it satisfying both parts and society. We will try to study the question in such a way to become the juridical ambient foreseeable, to proportion to the parts previous knowledge of the real scenery, (which is fixed while not changed), and that they can through this knowledge, plan their lives and assume their risks consciously. We will try, at the end, copying the human system, to propose a judiciary system that learns at first rationally the truth involved, secondly that applies the human intuition in the subject, thirdly that tries to conciliate the parts and reconstruct their communication assigning its proportion of reason considering that in many proceedings both parts have reciprocally errors and discernments to adjust being not totally right nor totally wrong what will not be almost never contemplate by the actual judicial sentence in the actual way of treating the subject and at hindmost, to apply the elaborate and refined Feeling to the judicial decisions in a way to content both parts involved more than the actual system does.